Analisis Dialektika Hegel dalam “Desak Anies”: Sebuah Pendidikan Demokrasi - Edel, Eky Erlanda; Syihabuddin; Sasnitya, Raden (Jurnal Sasindo UNPAM, 2024)
This research aims to analyze Anies Baswedan's thinking patterns, particularly during dialogues, using Hegelian Analysis, which emphasizes the process of thesis, antithesis, and synthesis in the dynamics of social-political conflict and resolution. This study also highlights the importance of democratic education in facilitating critical and in-depth understanding of political issues. The research employs a qualitative approach with content analysis and narrative analysis methods, using Hegelian Dialectics to identify the thesis, antithesis, and synthesis in Anies Baswedan's thoughts and the "Desak Anies" program in Semarang, as covered by MetroTV and uploaded in February 2024. Data collection techniques include literature review from various sources, content analysis of the "Desak Anies" program, and public documentation of the program on YouTube. Keywords: two or more important, specific, or representative words or phrases for the journal. Based on the results, Anies Baswedan typically answers questions in a structured dialogue format with standard composition: introduction, content, and conclusion. He does this to demonstrate his understanding of the thesis (initial condition), antithesis (opposing condition), and synthesis (improved condition). Throughout this process, Anies Baswedan always provides examples as reasoning to help his interlocutors understand the logic he wants to convey. Therefore, Anies Baswedan does not answer briefly because he tends to explain at length to ensure clarity. This approach fosters enthusiasm among the public, especially Millennials and Generation Z, to be politically aware; they are motivated to learn about Indonesian politics and to decide on the best future leaders for them. The concept of "Desak Anies" illustrates how democratic principles can be simply exemplified by a leader.